GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 20 Feb 2019, 10:09

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

## Events & Promotions

###### Events & Promotions in February
PrevNext
SuMoTuWeThFrSa
272829303112
3456789
10111213141516
17181920212223
242526272812
Open Detailed Calendar
• ### Free GMAT Prep Hour

February 20, 2019

February 20, 2019

08:00 PM EST

09:00 PM EST

Strategies and techniques for approaching featured GMAT topics. Wednesday, February 20th at 8 PM EST

February 21, 2019

February 21, 2019

10:00 PM PST

11:00 PM PST

Kick off your 2019 GMAT prep with a free 7-day boot camp that includes free online lessons, webinars, and a full GMAT course access. Limited for the first 99 registrants! Feb. 21st until the 27th.

# x(x – y) – z(x – y) =

Author Message
TAGS:

### Hide Tags

Math Expert
Joined: 02 Sep 2009
Posts: 53020
x(x – y) – z(x – y) =  [#permalink]

### Show Tags

01 Jun 2017, 11:10
00:00

Difficulty:

5% (low)

Question Stats:

88% (00:53) correct 12% (01:15) wrong based on 66 sessions

### HideShow timer Statistics

$$x(x – y) – z(x – y) =$$

(A) x – y
(B) x – z
(C) (x – y)(x – z)
(D) (x – y)(x + z)
(E) (x – y)(z – x)

_________________
Senior SC Moderator
Joined: 22 May 2016
Posts: 2487
x(x – y) – z(x – y) =  [#permalink]

### Show Tags

01 Jun 2017, 12:13
Bunuel wrote:
$$x(x – y) – z(x – y) =$$

(A) x – y
(B) x – z
(C) (x – y)(x – z)
(D) (x – y)(x + z)
(E) (x – y)(z – x)

$$x(x – y) – z(x – y) =$$

Factor out $$(x - y)$$ to get

$$(x - y) (x - z)$$

To double check work

Prompt: $$x(x – y) – z(x – y) =$$

$$(x^2 - xy) - (xz - yz)$$=

$$x^2 - xy - xz + yz$$

Answer: $$(x - y) (x - z)$$ =

$$x^2 - xz - xy + yz$$ - rearrange the two inner terms and it's a match
_________________

To live is the rarest thing in the world.
Most people just exist.

Oscar Wilde

Director
Joined: 04 Dec 2015
Posts: 740
Location: India
Concentration: Technology, Strategy
Schools: ISB '19, IIMA , IIMB, XLRI
WE: Information Technology (Consulting)
Re: x(x – y) – z(x – y) =  [#permalink]

### Show Tags

01 Jun 2017, 14:43
Bunuel wrote:
$$x(x – y) – z(x – y) =$$

(A) x – y
(B) x – z
(C) (x – y)(x – z)
(D) (x – y)(x + z)
(E) (x – y)(z – x)

Given $$x(x – y) – z(x – y) =$$
(x - y) is common factor, taking out the common factor we get;
(x - y)(x - z)
Target Test Prep Representative
Status: Founder & CEO
Affiliations: Target Test Prep
Joined: 14 Oct 2015
Posts: 4938
Location: United States (CA)
Re: x(x – y) – z(x – y) =  [#permalink]

### Show Tags

05 Jun 2017, 15:20
Bunuel wrote:
$$x(x – y) – z(x – y) =$$

(A) x – y
(B) x – z
(C) (x – y)(x – z)
(D) (x – y)(x + z)
(E) (x – y)(z – x)

Let’s simplify the given expression:

x(x - y) - z(x - y)

Factoring out (x- y), we have:

(x - y)(x - z)

_________________

Scott Woodbury-Stewart
Founder and CEO

GMAT Quant Self-Study Course
500+ lessons 3000+ practice problems 800+ HD solutions

CEO
Joined: 11 Sep 2015
Posts: 3440
Re: x(x – y) – z(x – y) =  [#permalink]

### Show Tags

05 Jun 2017, 15:29
Top Contributor
Bunuel wrote:
$$x(x – y) – z(x – y) =$$

(A) x – y
(B) x – z
(C) (x – y)(x – z)
(D) (x – y)(x + z)
(E) (x – y)(z – x)

The posters above me demonstrated the best/faster approach, BUT if you didn't think of that technique, you can still solve the question.
We're looking for an expression that is EQUIVALENT to x(x – y) – z(x – y)
So, for any set of values for x, y and z, the correct answer must evaluate to have the same value as x(x – y) – z(x – y)

So, let's plug in some values for x, y and z
Let's try x = 3, y = 1 and z = 10

First plug those values into the GIVEN expression.
We get: x(x – y) – z(x – y) = 3(3 – 1) – 10(3 – 1)
= 3(2) – 10(2)
= 6 - 20
= -14

So, the correct answer choice will be the one that evaluates to -14 when we plug in x = 3, y = 1 and z = 10
(A) x – y = 3 - 1 = 2. We want -14. ELIMINATE A
(B) x – z = 3 - 10 = -7. We want -14. ELIMINATE B
(C) (x – y)(x – z) = (3 - 1)(3 - 10) = (2)(-7) = -14. GREAT! KEEP C
(D) (x – y)(x + z) = (3 - 1)(3 + 10) = (2)(13)= 26. We want -14. ELIMINATE D
(E) (x – y)(z – x) = (3 - 1)(10 - 3) = (2)(7)= 14. We want -14. ELIMINATE E

By the process of elimination, the correct answer is

Cheers,
Brent

RELATED VIDEO

_________________

Test confidently with gmatprepnow.com

SVP
Joined: 06 Nov 2014
Posts: 1877
Re: x(x – y) – z(x – y) =  [#permalink]

### Show Tags

06 Jun 2017, 05:38
2
Bunuel wrote:
$$x(x – y) – z(x – y) =$$

(A) x – y
(B) x – z
(C) (x – y)(x – z)
(D) (x – y)(x + z)
(E) (x – y)(z – x)

We need to rearrange the terms in order to get the desired option.
On opening the brackets and rearranging, we get

x^2 - xy - zx + zy = x^2 - zx -xy + zy = x(x - z) - y(x - z) = (x - z)(x - y)

Correct Option C
Non-Human User
Joined: 09 Sep 2013
Posts: 9862
Re: x(x – y) – z(x – y) =  [#permalink]

### Show Tags

09 Feb 2019, 12:09
Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email.
_________________
Re: x(x – y) – z(x – y) =   [#permalink] 09 Feb 2019, 12:09
Display posts from previous: Sort by